ABCC3 is a novel target for the treatment of pancreatic cancer. (August 2019) - Adamska, Aleksandra; Ferro, Riccardo; Lattanzio, Rossano; Capone, Emily; Domenichini, Alice; Damiani, Verena; Chiorino, Giovanna; Akkaya, Begum Gokcen; Linton, Kenneth J.; De Laurenzi, Vincenzo; Sala, Gianluca; Falasca, Marco
Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) is a very aggressive disease, lacking effective therapeutic approaches and leaving PDAC patients with a poor prognosis. The life expectancy of PDAC patients has not experienced a significant change in the last few decades with a five-year survival rate of only 8%. To address this unmet need, novel pharmacological targets must be identified for clinical intervention. ATP Binding Cassette (ABC) transporters are frequently overexpressed in different cancer types and represent one of the major mechanisms responsible for chemoresistance. However, a more direct role for ABC transporters in tumorigenesis has not been widely investigated. Here, we show that ABCC3 (ABC Subfamily C Member 3; previously known as MRP3) is overexpressed in PDAC cell lines and also in clinical samples. We demonstrate that ABCC3 expression is regulated by mutant p53 via miR-34 and that the transporter drives PDAC progression via transport of the bioactive lipid lysophosphatidylinositol (LPI). Disruption of ABCC3 function either by genetic knockdown reduces pancreatic cancer cell growth in vitro and in vivo . Mechanistically, we demonstrate that knockdown of ABCC3 reduce cell proliferation by inhibition of STAT3 and HIF1α signalling pathways, previously been shown to be key regulators of PDAC progression. Collectively, our results identify ABCC3 as a novel and promising target in PDAC therapy.